Preliminary sizing of solar district heating systems with seasonal water thermal storage. Issue 2 (February 2022) - Hiris, Daniel P.; Pop, Octavian G.; Balan, Mugur C.
Abstract: The study proposes a method for preliminary and estimative sizing of the main components of solar district heating systems, with seasonal thermal storage. The main parameters determined by this method, are the aperture area of the solar thermal collectors and the volume of the seasonal thermal storage. The proposed method is only estimative, but it provides the necessary input data for the investigation ofthe dynamic thermal behavior of such systems. The main advantage of the method is that it requires only very few and accessible input data. Two situations are considered: the first in which available climatic data such as annual global solar radiation on horizontal plane and annual average temperature can be used in calculations, and the second in which such data is not available and should be determined through interpolation. With the proposed interpolation functions the annual global solar radiation on horizontal plane, the annual average temperature and the annual global efficiency of the solar thermal collectors were determined. The errors of the estimations are ranging within the intervals of (−15.6 … +25.8) % for annual global solar radiation on horizontal plane and (−10.8 … 19.1) % for annual global efficiency of the solar thermal collectors. The maximum deviations for the annual average temperature estimations were (−4.23 … +5.37) °C. With this limited accuracy, the proposed interpolation functions can be used for latitudes between (0–70) °, annual global solar radiation on horizontal plane between (704–2337) kWh/m 2 /year and annual average temperatures ranging within the interval of (2–30) °C. Abstract : Solar district heating, Seasonal thermal storage, Preliminary sizing, Web based application, Aperture area, Storage system volume.